DETERMINAN DIFERENSIASI PRODUK, BRAND IMAGE DAN INOVASI PRODUK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA LIPSTIK WARDAH DI KOTA SEMARANG - Widya, Sukma; Ariati Anomsari; Hertiana Ikasari; Diana Puspitasari (Universitas Pasundan, 2025)
The beauty industry in Indonesia is growing rapidly as public awareness of appearance increases, encouraging Wardah to innovate and build a strong brand image as a pioneer of halal cosmetics. This success is highly dependent on customer satisfaction as the link between product excellence and customer loyalty. This study uses a quantitative method with primary data from questionnaires and secondary data from relevant literature. The sample, consisting of at least 163 respondents, was purposively selected from the community of Semarang City who use at least three Wardah brand cosmetic and skincare products. Data analysis was performed using Partial Least Square (PLS) with SmartPLS software, including instrument validity and reliability tests, outer model, inner model through R square, hypothesis and mediation tests based on p-value with a significance level of 0.05. Based on the results of the direct effect analysis, it was found that product differentiation, brand image, and product innovation had a significant positive effect on customer satisfaction. In addition, customer satisfaction, product differentiation, and brand image were also found to have a significant positive effect on customer loyalty. However, product innovation did not have a significant effect on customer loyalty. Meanwhile, the results of the indirect effect analysis showed that customer satisfaction can mediate the effect of product differentiation, brand image, and product innovation on customer loyalty.